Bilateral fractures of femoral neck in patients with moderate renal failure receiving fluoride for spinal osteoporosis. Issue 6394 (10th September 1983) - Gerster, J C; Charhon, S A; Jaeger, P; Boivin, G; Briancon, D; Rostan, A; Baud, C A; Meunier, P J
Abstract : Two patients with moderate renal failure sustained spontaneous bilateral hip fractures during treatment with fluoride, calcium, and vitamin D for osteoporosis. They had been taking sodium fluoride (40-60 mg/day) for 11 and 21 months, respectively. Histological examination of a specimen of the bone showed severe fluorosis in the first case, and quantitative analysis of bone showed osteomalacia and skeletal fluorosis in the other case. These abnormalities were considered to be the consequence of excessive retention of fluoride due to renal insufficiency. As bilateral femoral neck fractures are very rare these data suggest a causal link between fractures and fluoride in patients with renal failure. Thus fluoride should be given at a lower dosage, if at all, to patients with even mild renal failure.